Roles of Hox genes in the patterning of the central nervous system of Drosophila - Estacio-Gómez, Alicia (Landes Bioscience, 2014)
One of the key aspects of functional nervous systems is the restriction of particular neural subtypes to specific regions, which permits the establishment of differential segment-specific neuromuscular networks. Although Hox genes play a major role in shaping the anterior-posterior body axis during animal development, our understanding of how they act in individual cells to determine particular traits at precise developmental stages is rudimentary. We have used the abdominal leucokinergic neurons (ABLKs) to address this issue. These neurons are generated during both embryonic and postembryonic neurogenesis by the same progenitor neuroblast, and are designated embryonic and postembryonic ABLKs, respectively. We report that the genes of the Bithorax-Complex, Ultrabithorax (Ubx) and abdominal-A (abd-A) are redundantly required to specify the embryonic ABLKs. Moreover, the segment-specific pattern of the postembryonic ABLKs, which are restricted to the most anterior abdominal segments, is controlled by the absence of Abdominal-B (Abd-B), which we found was able to repress the expression of the neuropeptide leucokinin. We discuss this and other examples of how Hox genes generate diversity within the central nervous system of Drosophila.